The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1063/1.1882772
|View full text |Cite
|
Sign up to set email alerts
|

Study of ferroelectric domain switching by domain wall induced light scattering

Abstract: The 90°-light scattering on domain walls was probed in various strontium barium niobate ͑SBN͒ crystals for studies of the ferroelectric switching under pulsed fields. The validity of this optical method is proved by a good agreement of the switching parameters deduced from optical scattering data with those obtained with electric methods. Scanning of the scattering over the crystal bulk revealed local specialities of the switching, particularly, a marked distribution of the domain wall density D along the pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…15 The dependencies I SHG ͑E͒ are controlled by the duration of the field pulses which is exemplified by Fig. Actually, they are close to E c determined in this crystal by the traditional methods.…”
supporting
confidence: 65%
“…15 The dependencies I SHG ͑E͒ are controlled by the duration of the field pulses which is exemplified by Fig. Actually, they are close to E c determined in this crystal by the traditional methods.…”
supporting
confidence: 65%
“…Previous studies, have shown how the ferroelectric domain structure in as-grown SBN crystals, plays a fundamental role on the scattering of radiation emerging in the plane perpendicular to the c axis. [17,[21][22][23] This scattering has been related to the ferroelectric domain structure, in particular to inhomogeneities of the refractive index at the domain walls. The diffuse nature of radiation detected in the plane perpendicular to the c axis has been reported for the fundamental beam as well as for second order generated radiation.…”
Section: Collinear Configurationmentioning
confidence: 99%
“…In fact, the scattering of fundamental radiation has been probed in various SBN crystals for studies of the ferroelectric switching. [23] The domain wall induced light scattering has been also associated with the diffuse nature of the planar SH radiation observed in intra or extra cavity frequency conversion processes. [24] However, no experimental confirmation supporting the later fact has been reported up to now.…”
Section: Collinear Configurationmentioning
confidence: 99%
“…Possible mechanisms that increased the optical transmission by La‐doping were associated with changes in microstructure and/or domain structure . To determine which factor was more important, the microstructures were initially studied.…”
Section: Resultsmentioning
confidence: 99%